Extraction of CNSL using screw press - Chaudhari, Ashok Pralhad; Thakor, Nayansingh Jaswantsingh (Asian Journal of Biological and Life Sciences, 2015)
Liquid from Cashew Nut shell is generally extracted by three methods namely, mechanical, roasting and solvent extraction. The expeller (mechanical) process of oil extraction is more feasible for adoption on industrial scale. The influence of moisture content of cashew nut shells on the extraction of CNSL (Cashew Nut Shell Liquid) by screw press method was studied to find out the role of moisture content in the oil yield and there by optimising the moisture content of shells for the extraction process. The estimation of oil content in the cashew nut shells was carried out using a Soxhlet apparatus. The experiments were conducted at four different levels of moisture (8.12, 10.06, 12.17 and 14.20% (wb)) for the extraction of CNSL by screw press method. Average oil content in cashew nut shells was found to be 26.45%. This CNSL content of cashew nut shells implies that there is a good scope for processing the shells for oil. It would be economical instead of directly using as fuel. The moisture content of the cashew nut shells at the time of extraction (% recovery) of CNSL has a great influence on the oil recovery. It is found that 10.06% moisture content Wet basis(wb)) in cashew nut shells is the optimum moisture content for extraction of oil from cashew nut shells in order to get the maximum oil recovery of 86.68%.
Keywords: Cashew nut shells; Extraction of CNSL; Oil content; Screw press